Longman dictionary of business English - Adam, J. H.; Arnold, David (Harlow, Essex : Longman ; Beirut : York Press, 1989)
The dictionary is a complete and up-to-date guide to the language of business and commerce. It provides clear and comprehensive definitions and examples of the terms used in buying and selling, in banking, finance, insurance and shipping- the language of commerce and economics textbooks, newspapers, journals, company reports and commercial law.
First edition: 1982.
ne 23/09/2021
Ref.
Keywords: Business; Commerce; English language